-12x-2y≥-42

Add 12x to both sides of the inequality.

-2y≥-42+12x

Divide each term in -2y≥-42+12x by -2. When multiplying or dividing both sides of an inequality by a negative value, flip the direction of the inequality sign.

-2y-2≤-42-2+12x-2

Cancel the common factor of -2.

Cancel the common factor.

-2y-2≤-42-2+12x-2

Divide y by 1.

y≤-42-2+12x-2

y≤-42-2+12x-2

Simplify each term.

Divide -42 by -2.

y≤21+12x-2

Cancel the common factor of 12 and -2.

Factor 2 out of 12x.

y≤21+2(6x)-2

Move the negative one from the denominator of 6x-1.

y≤21-1⋅(6x)

y≤21-1⋅(6x)

Rewrite -1⋅(6x) as -(6x).

y≤21-(6x)

Multiply 6 by -1.

y≤21-6x

y≤21-6x

y≤21-6x

Solve for y -12x-2y>=-42